Factors associated with low-density lipoprotein control in outpatients with myocardial infarction: A hospital-based study - Anan S. Jarab; Walid Al-Qerem; Razan Mansour; Hamza Jarab; Shrouq R. Abu Heshmeh; Omar Jrab; Abdullah Elrefae; Yazid N. Al Hamarneh; Ahmad Z. Al Meslamani; Salahdein Aburuz (PLoS ONE, 2026)
Discrepancies in factors influencing low-density lipoprotein cholesterol (LDL-C) control in patients with myocardial infarction have been documented in existing literature. Assessing LDL-C control and the associated factors is a crucial initial measure for guiding future interventions aimed at enhancing health outcomes in patients with myocardial infarction (MI). This study aimed to evaluate LDL-C control status and explore the predictors of uncontrolled LDL-C in patients with myocardial infarction. Data were collected by a research pharmacist from medical records, including sociodemographic and clinical characteristics, comorbidities, prescribed medications, and biomedical parameters such as LDL-C levels among patients attending an outpatient cardiology clinic. The validated Arabic versions of the 4-item medication adherence scale and the medication beliefs questionnaire were used to evaluate medication adherence and beliefs, respectively. Binary logistic regression was implemented to investigate the predictors of LDL-C control. The results showed most of the patients (n = 255) had uncontrolled LDL-C (76.6%). Regression results revealed that smoking (OR= 2.006; 95% CI: 1.054–3.816; P = 0.034), receiving beta blockers (OR=2.211; 95% CI: 1.024–4.775; P = 0.043), and having uncontrolled blood pressure (OR=1.940; 95% CI: 1.069–3.520; P = 0.029) were independently associated with higher odds of uncontrolled LDL-C. In conclusion, in MI patients with poor LDL-C control, lowering the risk of cardiac complications and improving health outcomes require the development of focused and efficient LDL-C level management strategies. Achieving this goal will require putting strategies like smoking cessation counselling into practice and improving BP control.